(untitled) (Revista Argentina de Cirugía, 2021)
Background: Despite laparoscopic liver resection has significantly evolved, most hepatectomies are performed by the conventional approach. Objective: The aim of this study is to present the initial experience and applicability of laparoscopic liver resections. Material and methods: We conducted a retrospective analysis of patients undergoing liver resection between August 2010 and December 2019. Perioperative, intraoperative and postoperative variables were analyzed. To evaluate applicability, the sample was divided into 3 stages: stage 1, from August 2010 to December 2013; stage 2, from January 2014 to December 2016; and stage 3, from January 2017 to December 2019. Results: Of 385 liver resections performed, 119 were laparoscopic procedures: 53 (44%) were pure laparoscopic procedures, 64 (54%) were hand-assisted (64 patients) and 2 corresponded to hybrid procedures. Global applicability was 31%. In stage 1 1: 23%, in 2: 30% and in 3: 44% (p < 0.05). Malignant lesions: stage 1: 36%, stage 2: 67% and stage 3: 72% (p < 0.05). Major liver resections: 13%, 31% and 32% in stages 1, 2, and 3, respectively (p < 0.05). Conversion rate was 12%, 0% and 11%, respectively (p NS). Hepatic pedicle clamping was used in 6%, 5% and 45%; (p < 0.05). Complications in stage 1 were 30%, in stage 2: 28% and in stage 3: 17%, and Clavien-Dindo complications grade 3 or greater were 6%, 13% and 5%, respectively, p NS. Conclusions: Laparoscopic liver resections are complex procedures but technically reproducible. Applicability increases with the acquisition of experience.